Financing micro, small, and medium enterprises : an independent evaluation of IFC's experience with financial intermediaries in frontier countries (IFC WashingtonUS, 2008)
Assesses International Finance Corporation's strategies, investment projects and advisory services operations during FY94 - FY06 to support micro, small and medium-size enterprises in frontier countries.
Keywords: FINANCING